A CoN‐based OER Electrocatalyst Capable in Neutral Medium: Atomic Layer Deposition as Rational Strategy for Fabrication. (9th April 2021) - Guo, Daying; Zeng, Zhihao; Wan, Zhixin; Li, Yan; Xi, Bin; Wang, Chengxin
Abstract: Reported herein is an active and durable CoN‐containing oxygen evolution reaction (OER) electrocatalyst which efficiently functions in a neutral medium (pH ≈7). The composite material (N, S)‐RGO@CoN is synthesized by delicate atomic layer deposition (ALD) of CoN on a nitrogen and sulfur (N, S) co‐doped reduced graphene oxide (RGO) substrate. Representative results of the comprehensive study are: 1) The flower‐like sphere RGO substrate prepared by spray drying method features rich physical and chemical properties, which are beneficial for rapid mass/charge transfer to improve the intrinsic OER process; 2) the optimal ALD material for OER tests is afforded by tuning spray conditions and ALD parameters. Versatile structural and compositional characterizations confirm uniform growth and strong chemical coupling of nanostructured CoN on (N, S)‐RGO matrix; 3) the material is electrocatalytically active and durable in a neutral electrolyte, recording an OER overpotential of 220 mV at a current density of 10 mA cm −2 and stability of 20 h continuous catalysis at 20 mA cm −2 with nearly 100% Faradic efficiency; 4) Upon the experimental studies and density functional theory calculations, the eventual mechanism of remarkable OER activity conforms to the structural fate of ALD CoN electronic coupling to the carbon substrate. Abstract : Delicate atomic layer deposition of CoN on a nitrogen and sulfur co‐doped reduced graphene oxide substrate affords an active and durable oxygen evolution reaction electrocatalyst, which is capable in a neutral medium.